2021
DOI: 10.1017/s1460396921000467
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of dose volumetric parameters of oesophagus in the radiation treatment of carcinoma breast with and without oesophagus delineation

Abstract: Aim: There are only limited studies available in literature that discuss methods to reduce the oesophageal dose and acute oesophagitis during breast cancer radiotherapy. The aim of this study is to compare dose volumetric parameters of oesophagus in radiation treatment of breast with and without oesophagus delineation. Methods: Treatment plans of 44 patients, who underwent chest wall and supraclavicular fossa irradiation, were selected for the study. Oesophagus was later delineated and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…D mean was 14•11±4•24Gy in the without oesophagus delineation group. A higher mean dose and V 15 in their study may be due to the contouring oesophagus at risk as they delineated the oesophagus from the room caudal border of the cricoid cartilage to the lower border of supraclavicular PTV (13) .…”
Section: Discussionmentioning
confidence: 91%
“…D mean was 14•11±4•24Gy in the without oesophagus delineation group. A higher mean dose and V 15 in their study may be due to the contouring oesophagus at risk as they delineated the oesophagus from the room caudal border of the cricoid cartilage to the lower border of supraclavicular PTV (13) .…”
Section: Discussionmentioning
confidence: 91%
“…The left SCF is closer to the esophagus and may overlap it because of the esophagus's slight deviation to the left during its descent. In contrast to the right-sided SCF, this may lead to higher radiation dosages reaching the esophagus [ 23 ]. During our study, we found that the left side of the esophagus had higher D max and D mean values (6.7±2.1 Gy and 39.2±1.5 Gy, respectively) than the right side.…”
Section: Discussionmentioning
confidence: 99%
“…This occurrence could be explained by the left-sided position of the esophagus relative to the SCF. Bhaskaran et al's study reveals that left-sided breast cancer exposes the esophagus to more radiation than right-sided breast cancer, which might cause an imbalance in the radiation dose that these two regions receive [ 23 ]. If someone has regular esophageal shaping, the right amount of radiation exposure, close patient monitoring during RT for esophageal inflammation, and good treatment process management [ 24 ], it is less likely that they will develop esophagitis.…”
Section: Discussionmentioning
confidence: 99%
“…This could result in more dose received to the esophagus compared to the right side, this was in accordance with the result of a study carried out by Bhaskaran et al ., which reported that the dose delivered to esophagus is higher in the left-sided breast cancer. [ 20 ]…”
Section: Discussionmentioning
confidence: 99%